2019
DOI: 10.1029/2018jc014535
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Internal Variability on Ocean Temperature Adjustment in a Low‐Resolution CESM Initial Condition Ensemble

Abstract: Due to its large heat capacity and circulation, the ocean contributes significantly to global heat uptake, global heat transport, spatial temperature patterns, and variability. Quantifying ocean heat uptake across different temporal and spatial scales is important to quantify Earth's climate response to anthropogenic warming. Here we evaluate ocean adjustment time scales from two different fully coupled climate model ensembles using the Community Earth System Model. Both ensembles use the same model version, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Vertical distributions of physical and biogeochemical tracers take hundreds to thousands of years to achieve steady‐state for a given climate state (DeVries & Primeau, 2011; Sarmiento & Gruber, 2006). Ocean temperature and density perturbation adjustment timescales vary by depth and ocean basin, and are a function of the ocean's internal variability and key circulation components such as MOC, which are in turn affected by climate perturbations (Hogan & Sriver, 2019). The ocean response to such perturbations is asymmetric, with a generally faster response to cooling than to warming due to cooling‐enhanced convection and overturning (Yang & Zhu, 2011), as seen in our simulations.…”
Section: Discussionmentioning
confidence: 99%
“…Vertical distributions of physical and biogeochemical tracers take hundreds to thousands of years to achieve steady‐state for a given climate state (DeVries & Primeau, 2011; Sarmiento & Gruber, 2006). Ocean temperature and density perturbation adjustment timescales vary by depth and ocean basin, and are a function of the ocean's internal variability and key circulation components such as MOC, which are in turn affected by climate perturbations (Hogan & Sriver, 2019). The ocean response to such perturbations is asymmetric, with a generally faster response to cooling than to warming due to cooling‐enhanced convection and overturning (Yang & Zhu, 2011), as seen in our simulations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they showed that in several areas the internal ocean variability is more significant than atmospheric variability as a contribution to climate variability for both "the low-frequency variability and the long-term trends of regional ocean heat content". Similarly, in the study by Hogan and Sriver (2019) it was shown that internal variability is fundamental in setting the time scale for the ocean temperature adjustment process, increasing the speed at which the ocean takes up heat from the atmosphere, that is instead highly underestimated by just considering atmospheric variability. Lastly, as regards the scale dependency of the internal variability, it was demonstrated by Tang et al (2019) that by increasing the horizontal spatial resolution of ocean models more intrinsic variability is produced and, similarly, by analyzing the ratio of the externally forced over the internally generated variability (Tang et al (2020)) in the South China Sea, the external forcing is dominant for large scales, while most of the variability is internally generated for small scales.…”
mentioning
confidence: 99%